Tabloidyzacja prasy opiniotwórczej na przykładzie artykułów publicystycznych w tygodniku „Wprost” - Kasiak, Mateusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
Article is focused on the problem of tabloidisation of contemporary opinion journalism. The author argues with traditional understanding of tabloid, showing as an example tabloidisation of weekly opinion. The aim of the article is to show how the tabloidisation in journalistic articles of weekly “Wprost” looks like. The phenomenom of tabloidisation is illustrated based on the analysis of articles describing Kamila Durczok. How the tabloidisation was achieved there? It is more than one way. Analyses of texts show a few methods. Both the choice of subject and the construction of text, visual structure and language of text determine the tabloidisation. Analyses show also the real functions of using tabloidisation in the weekly opinion.